Useful technique for draining a large cystic tumor through the round ligament in laparoscopic left hemihepatectomy. Issue 2 (12th December 2018) - Monden, Kazuteru; Sadamori, Hiroshi; Hioki, Masayoshi; Ohno, Satoshi; Sasaki, Kyo; Saneto, Hiromi; Ueki, Toru; Yabushita, Kazuhisa; Sakaguchi, Kousaku; Takakura, Norihisa
Abstract: Introduction: Some cystic liver tumors are huge when the diagnosis is made or surgery is needed. Although reducing tumor size by preoperative aspiration or drainage of the contents of the cystic tumor is helpful for liver resection, such procedures have a risk of tumor dissemination. Materials and Surgical Technique: After the round ligament was dissected, a 12‐Fr drainage catheter was inserted into the tumor via the round ligament under ultrasonography. At that time, close attention was paid to avoid having the catheter deviate outside the round ligament. Through the inserted catheter, fluid was drained from the cystic lesion, and the stump of the round ligament was clipped to avoid fluid leakage. The left Glissonian pedicle was then taped. Laparoscopic left hemihepatectomy was performed under a good operative field because of tumor shrinkage. Discussion: Three cases underwent these procedures without any spillage of the contents of the cystic tumor. This method is useful for the reduction of tumor size and has a low risk of intra‐abdominal leakage of the contents, resulting in a secure and good operative field.